Local Infiltration Analgesia Compared With Epidural and Intravenous PCA After Surgical Hip Dislocation for the Treatment of Femoroacetabular Impingement in Adolescents. Issue 1 (January 2018) - Novais, Eduardo N.; Kestel, Lauryn; Carry, Patrick M.; Sink, Ernest; Strupp, Kim
Abstract : Background: Open treatment of femoroacetabular impingement (FAI) through a surgical hip dislocation (SHD) approach has been reported to allow for improvement in pain and function. However, the approach require a trochanteric osteotomy and may be associated with high level of pain after surgery. Currently, there is no systematic approach for pain management after SHD for treatment of FAI. Methods: A retrospective chart review was used to collect data from 121 subjects (12 to 21 y and below) who received periarticular local infiltration analgesia (LIA, n=20), epidural analgesia (n=72), or intravenous patient-controlled analgesia (PCA, n=29) after SHD from January 2003 to June 2014. Verbal pain scores, opioid consumption, incidence of side effects/complications, and length of hospital stay (LOS) were recorded. All nonopioid medications with analgesic potential were included in the statistical models as potential confounding variables Results: Twelve hours after surgery, the odds of moderate/severe pain were higher in the PCA group (odds ratio, 20.5; 95% confidence interval (CI), 1.7-243.8; P =0.0166] and epidural group (odds ratio, 5.2; 95% CI, 0.7-92.0; P =0.3218) compared with the LIA group. There was no difference in pain scores across all groups 1 hour ( P =0.0675) or 24 hours ( P =0.3473) postoperatively. Total opioid consumption in the LIA group was 59.8% (95% CI, 15.0%-81.0%; P =0.0175) lower than the total opioid consumption in the epidural group and 60.7% (95% CI, 17.3-81.3; P =0.0144) lower than the total opioid consumption in the PCA group. LOS was increased in the epidural (mean difference, 22.1; 95% CI, 6.8-37.4 h; P =0.0051) and PCA (mean difference, 16 h; 95% CI, 1-31.5 h; P =0.0367) groups relative to the LIA group. There was 0 (0%) complication in the LIA group compared with 11 (15.3%) in the epidural group. Conclusions: LIA was more effective at controlling pain 12 hours after surgery in comparison with PCA with similar pain control to epidural. LIA was associated with significantly lower need for opioids and shorter LOS compared with the PCA and epidural protocols. Periarticular infiltration should be considered for pain management after SHD for treatment of FAI in adolescents. Level of Evidence: Level III—retrospective comparative study.